1990
DOI: 10.21273/hortsci.25.8.930
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Selected Two-component Container Media

Abstract: Component and particle-size effects on shrinkage of two-component potting media were determined. Milled pine bark-sand mixtures were used to determine particle-size effects on shrinkage. Shrinkage curves formed an inverted V with maximum shrinkage at the 1:1 (v/v) ratio. No shrinkage occurred when bark was mixed with bark or sand with sand. Shrinkage increased linearly in the range of 0% to 50% bark and decreased linearly in the range of 50% to 100% bark. Each half of the shrinkage curve was a mirror i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Shrinkage after 70 weeks was highest in fallow PTS at both fertilizer rates (22.3% and 24.4%), but shrinkage in PTS that contained plants was equal to PB with plants (Table 2). Shrinkage results from particle size breakdown (microbial decomposition) and sub-strate settling (finer particles fit between larger particles) caused by gravity and water movement through the substrate during irrigations (Bilderback and Lorscheider, 1995;Bures et al, 1993;Nash and Pokorny, 1990). Substrate shrinkage causes a decrease in AS and an increase in CC over time as observed in this study (Table 2) and reported in other works (Bohne and Gunther, 1997;Prasad and Chualain, 2005).…”
Section: Resultssupporting
confidence: 77%
“…Shrinkage after 70 weeks was highest in fallow PTS at both fertilizer rates (22.3% and 24.4%), but shrinkage in PTS that contained plants was equal to PB with plants (Table 2). Shrinkage results from particle size breakdown (microbial decomposition) and sub-strate settling (finer particles fit between larger particles) caused by gravity and water movement through the substrate during irrigations (Bilderback and Lorscheider, 1995;Bures et al, 1993;Nash and Pokorny, 1990). Substrate shrinkage causes a decrease in AS and an increase in CC over time as observed in this study (Table 2) and reported in other works (Bohne and Gunther, 1997;Prasad and Chualain, 2005).…”
Section: Resultssupporting
confidence: 77%
“…Media containing high proportion of kenaf core fiber (T 5 ) have a higher rate of water absorption (b = 0.798) and ended-up with a significantly higher moisture content than the medium with 70% cocopeat and 30 kenaf core fiber (T 4 , b = 0.401). High water absorption by this medium may be due the settling effect upon wetting which reduces column height and changes the distribution between the capillary and noncapillary pores [15] . In the process, small particles settle into large non-capillary pores located between the larger particles.…”
Section: Resultsmentioning
confidence: 99%
“…settling and compression caused by gravity and water movement through the substrate during irrigations (Fonteno et al, 1981;Meinken and Fischer, 1997). When particles of different sizes are mixed, shrinkage of the final volume occurs, because small particles fill the pores located between the large particles (Bures et al, 1993;Nash and Pokorny, 1990). Effects on poinsettia growth, floral quality, and postproduction time to wilting.…”
Section: Resultsmentioning
confidence: 99%